Análisis de la comercialización de la Empresa Comercial Cervantes en la ciudad de Guayaquil - Cervantes Briones, Erik Fernando (2024)
The main objective of this thesis is to analyze the factors that influence the commercialization of the company Comercial Cervantes in the city of Guayaquil. For this purpose, a data collection methodology was used by means of surveys to 30 customers in the southern sector of Guayaquil, specifically in the Ximena parish. The analysis of these surveys provided valuable information on consumer preferences and the effectiveness of the credit financing strategies implemented by the company. The study included a cross-matrix SWOT analysis to identify Comercial Cervantes' strengths, opportunities, weaknesses, and threats. Strengths include product quality and customer service, while opportunities include market growth and expansion into new segments. The weaknesses identified are related to limited promotional capacity and dependence on a specific market, while the threats include high competition and economic instability. The results of the SWOT analysis enabled the development of SWOT (Strengths-Opportunities), SWOT (Strengths-Threats), SWOT (Weaknesses-Opportunities) and SWOT (Weaknesses-Threats) strategies to maximize strengths and opportunities, and mitigate weaknesses and threats. In conclusion, the study provides a comprehensive view of the challenges and opportunities faced by Comercial Cervantes, and offers recommendations for improvement.